Coffee productive and vegetative traits characteristics under different deletions of irrigation and side exposure to sun - Custódio, Anselmo Augusto de Paiva; Lemos, Leandro Borges; Mingotte, Fábio Luiz Checchio; Cunha, Tatiana Pagan Loeiro da; Carmeis, Antônio Carlos de Almeida; Barbosa, José Carlos (Coffee Science - ISSN 1984-3909, 2014)
The objective of this study was to verify the initial effects of different deletions of irrigation on vegetative and productive characteristics of coffee after pruning. The experiment in split plot design with four replications in a randomized complete block design was conducted at Fazenda Cambuhy Agrícola Ltda (Matão, state of São Paulo), with arabica cultivar Mundo Novo IAC 376-4, in a drip system in the 2010/2011 season. For the vegetative characteristics, primary treatment consisted of six deletions irrigation NI = not irrigated, IC = continuous irrigation throughout the year, IC = IC 14a-19m, except between April 14 to May 19, IC-20m 24jn = IC, except between May 20 to June 24, IC-25jn 30jl = IC, except between June 25 to July 30 and IC = IC 31jl-04s, except between July 31 to September 4. Secondary treatments mentioned up to six evaluation periods. For production traits primary treatments were deletions in irrigation treatments and the secondy treatment checks for side of plant exposure to solar radiation Southeast (SE) and northwest (NW). We evaluated the vegetative characteristics and canopy stem diameter, plant height and insertion of the first branch, number of branches and length of branches (SE, NW and middle). The total productivity of coffee and enjoyed the “floor”, crop yield, income benefit and weight of 100 grains was evaluated on each face exposure. The non-irrigated coffee has the lowest increase in initial growth after pruning, except for insertion height of the 1st. plagiotrophycal. In irrigated coffee throughout the year, the lowest increase in the initial growth occurs with greater suppression IC 25jn-30jl e IC 31jl-04s, during the spring and summer, except for the canopy diameter. In irrigated coffee trees, especially the use of deletions IC 20m-24jn, and IC-25jn 30jl, higher overall productivity and income benefit of coffee occurs, compared to non-irrigated coffee. The northwest face of plant exposure to solar radiation provides higher total yield and yield of coffee.